2012
DOI: 10.1111/j.1439-0272.2012.01278.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma testosterone in adult normoglycaemic men: impact of hyperinsulinaemia

Abstract: This study analysed the relationship of plasma testosterone with β-cell secretion, insulin sensitivity and other pituitary-target gland hormones in normoglycaemic adult men. The sample frame was the 'Offspring of individuals with diabetes study' database. A total of 358 offspring of individuals with type-2 diabetes (T2DM) and 287 individuals without known family history of T2DM were recruited for the study. Normoglycaemic men aged ≥18 years (maximum 55) were selected for this analysis. All participants underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…In the present study, we found, apart from an inverse correlation between (free) T and SAT cell size in univariate analyses, an inverse association of (free) T levels with TG and insulin sensitivity (HOMA-IR). Inverse associations between T levels and TG are consistent with the findings of previous studies [ 29 , 30 ]. Elevated circulating TG levels have been suggested to be an indicator of metabolic derangement, associated with both glucose intolerance and increased amounts of VAT [ 31 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we found, apart from an inverse correlation between (free) T and SAT cell size in univariate analyses, an inverse association of (free) T levels with TG and insulin sensitivity (HOMA-IR). Inverse associations between T levels and TG are consistent with the findings of previous studies [ 29 , 30 ]. Elevated circulating TG levels have been suggested to be an indicator of metabolic derangement, associated with both glucose intolerance and increased amounts of VAT [ 31 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…Plasma cortisol was higher among subjects with impaired glucose tolerance. There was positive association of testosterone with cortisol and insulin sensitivity in adult normoglycemic men [14]. A large population-based study reported that the presence of metabolic syndrome was associated with lower AUC of cortisol [15].…”
Section: Introductionmentioning
confidence: 97%